Artists in Architecture : Re-Activating Modern European Houses. - Weyts, Kathleen; Lauwers, Sophie; Carpentier, Francis; Dumartheray, Emma; Crabbé, Sofie; Swinnen, Peter; Cicek, Asli; Puente, Moisés; Strauven, Iwan ([S.l.] : HART Magazine, 2019)
Strebelle, Olivier ; Van Der Meeren, Willy ; Iancu, Marcel ; Illescas, Sixte ; LeWitt, Sol ; Castellano, Umberto ; Pane, Andrea
Artists in Architecture. Re-Activating Modern European Houses, Centre for Fine Arts, Brussels, 13.11.2019 until 12.01.2020
boek